Street food in Maputo, Mozambique: The coexistence of minimally processed and ultra-processed foods in a country under nutrition transition - Sousa, S (2021)
The aim was to characterise the extent of processing and nutritional composition of the street foods offered in Maputo, Mozambique. A cross-sectional study was conducted in October November 2014 in the urban district of KaMpfumu. Twenty public transport stops were randomly selected, around which 500 meters buffers were drawn. All streets within these buffers were can-vassed to identify all street food vending sites. Street food offer was assessed through interviews. Nutritional composition was estimated using standardised recipes (for homemade foods), food labels (for industrial products) and food composition tables (for in natura foods). The processing extent was classified using the NOVA food classification. A total of 810 vending sites were assessed. Unprocessed/minimally processed foods were available at 70.5% of vending sites (mainly fruit, water, and tea) and ultra-processed foods at 59.0% (mostly cakes, cookies, confectionery, and soft drinks). Energy content per 100 g of unprocessed or minimally processed foods was significantly lower than in all other food groups. In all food groups, contribution to total energy value was highest for carbohydrates (range: 33.151.2%), followed by fats (range: 29.336.0%) and protein (range: 6.818.6%). Public health policies targeting the improvement of this urban food environment should consider not only the nutritional composition but also the processing extent of the foods and beverages available. (c) 2021 by the authors. Licensee MDPI, Basel, Switzerland.